Evidence for measurement of overlap between Autism Spectrum Disorder and Attachment Disorder - JOANNA DAVIES (2022)
The extent of overlapping presentation within Attachment Disorder (AD) and Autism Spectrum Disorder (ASD) gives rise to considerable difficulties for the separation of the disorders. In order to ascertain the impact of the difficulties in differentiating the symptomologies on diagnosis, this study was designed to seek to measure the presenting behaviours of children using psychometric tools with a view to contributing to the understanding of the commonalities, differences and the relationship between ASD and AD. Chapter 2 explored that a percentage of children with ASD meeting the criteria for AD. It was possible to discriminate between the presence or absence of ASD, and of AD, by the presence of all behavioural problems but ASD and AD could not be discriminated from one another either when predicting clinical diagnosis or psychometric classification. There was an indication that when using clinical diagnosis, hyperactivity was more predictive of AD than ASD. The research gave strength to the argument that overlap between ASD and AD exists. Chapter 3 considered overlaps and differences between parent reports of ASD and AD, and examined profiles of children fulfilling criteria for ASD and AD in terms of behaviour problems and attachment styles. There was a large overlap in the reported diagnoses and classifications of ASD and AD. Peer problems predicted a reported ASD diagnosis and conduct problems predicted a reported AD diagnosis. Attachment styles differentiated the diagnosis of those with ASD showing more ambivalent, and those with AD more avoidant and anxious, attachment styles. Chapter 4 compared the similarities and differences in parenting stress and behaviours in parent reports of ASD and AD. Parents of children with AD reported greater levels of parenting stress than parents of children with ASD. Parents of children reaching criteria for both disorders reported the greatest levels of parenting stress. Limit setting was poorest in parents of children with both classifications, followed by parents of children with AD and then ASD. Limit setting mediated the relationship between parenting stress and child behaviour problems for parents of children with ASD, but not for parents of children with AD. Chapter 5 investigated the differences between ASD and AD using Executive Function (EF) tasks in terms of their clinical diagnoses and psychometric traits, on four EF tasks (Wisconsin Card Sorting Task (WCST), Hungry Donkey, Stroop, and Tower of London). Limited difference between the EF performances of individuals with ASD and AD was noted (there was slightly better AD performance on cold EF tasks, and slightly better performance for ASD on hot tasks). Chapter 6 examined whether EF mediated the relationship between either ASD or AD, and behaviour problems, examined in terms of their AD and ASD traits, their levels of behaviour problems, and performance on four EF tasks (WCST, Hungry Donkey, Stroop, and Tower of London). There were positive correlations between levels of ASD and AD, and between both of these traits and behaviour problems. However, there was no relationship between these traits and EF and no relationship between EF and behaviour problems.